Sejarah Islamisasi dan Pengaruhnya Terhadap Kebudayaan Masyarakat Jambi - Sintya, Dinda; Sinurat, Junita Yosephine (Prabayaksa: Journal of History Education, 2024)
The Islamization process that occurred in Jambi coincided with the growth and development of the Islamic kingdom of Jambi around the 15th century AD. This article explains the history of Islamization which has had an influence on the culture of the Jambi people to this day. The method used in this research is a historical research method which is divided into four parts, namely Heuristics, Source Criticism, Interpretation and Historiography. The entry of Islam into the Jambi community was brought by adherents of the Islamic faith who came from Arab ethnicity, through trade that passed through waterways by sailing along the Batanghari river. The Islamization process in Jambi has had a big influence on the cultural development of the local community. The influence of Islamization on culture in Jambi can be seen from religious ceremonies commemorating Islamic holidays, marriage practices, art, social systems and architectural styles.